ANALISIS BALAGHAH TERHADAP HADIS NIAT DALAM ARBA'IN NAWAWI: KAJIAN STRUKTUR BAHASA DAN IMPLIKASI TEOLOGIS - Ramdani Nopandri; Mely Rahmadani; Nizar Ali (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2026)
This study examines the rhetorical dimensions (balaghah ) of the first hadith in Imam al-Nawawi's Arba'in, namely the hadith on intention (niyyah)